Lanreotide vs octreotide LAR for patients with advanced gastroenteropancreatic neuroendocrine tumors: An observational time and motion analysis. (September 2019) - Ryan, P; McBride, A; Ray, D; Pulgar, S; Ramirez, RA; Elquza, E; Favaro, JP; Dranitsaris, G
Background: Lanreotide and octreotide acetate suspension for injectable (LAR) are both recommended for clinical use in patients with locally advanced or metastatic gastroenteropancreatic neuroendocrine tumors. However, each agent possesses unique attributes in terms of their drug-delivery characteristics. The study objective was to compare overall drug-delivery efficiency between lanreotide and octreotide LAR in gastroenteropancreatic neuroendocrine tumor patients. Methods: This study employed an observational time and motion design among patients treated with lanreotide or octreotide LAR across five US cancer centers. Baseline patient data collection included age, disease grade and duration, prior therapies and performance status. Drug-delivery time (drug preparation and administration), total patient time and resource use data were collected for gastroenteropancreatic neuroendocrine tumors receiving lanreotide (n = 22) or octreotide LAR (n = 22). Following each administration, qualitative data on the drug-delivery experience was collected from patients and nurses. Results: Lanreotide was associated with a significant reduction in mean delivery time (2.5 min; 95% CI:2.0 to 3.1) compared to octreotide LAR (6.2 min; 95%CI: 4.4 to 7.9; p  = 0.004). The mean total patient time for lanreotide and octreotide LAR was comparable between groups (32.1 vs. 36.6 minutes; p  = 0.97). Nurses reported increased concerns with octreotide LAR related to needle clogging ( p  = 0.034) and device failures ( p  = 0.057). Overall, lanreotide had a median satisfaction score of 5.0 compared to a score of 4.0 with octreotide LAR ( p  = 0.03). Conclusions: Lanreotide was associated with significant reductions in drug-delivery time compared to octreotide LAR, which contributed to an improvement in overall healthcare efficiency. Trial registration: clinicaltrials.gov Identifier: NCT03017690.